ANALISA METODE PENCARIAN HASH - Imelda Sri Duma Yanti (METHODIKA: Jurnal Teknik Informatika dan Sistem Informasi, 2016)
Hash Methods Search efficiency use of a better place. Search relative (Hash Search) is divided into two kinds, namely Hash Closed (Closed Hashing) and Hash Open (Open Hashing). On Closed Hash there is the possibility of more than one data has a value the same function, causing a collision (collision). The way to overcome this collision can be done with some strategies such as, Resolution Linear (Linear Resolution), and Double Hashing Overflow. Each - each strategy has its advantages and disadvantages